2013
DOI: 10.1089/acm.2011.0593
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of T'ai Chi Exercise on Immunity and Infections: A Systematic Review of Controlled Trials

Abstract: TC exercise appears to improve both cell-mediated immunity and antibody response in immune system, but it remains debatable whether or not the changes in immune parameters are sufficient to provide protection from infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…T'ai chi ch'uan, an ancient Chinese martial art form that has recently come into vogue in western society has been subject to multiple studies investigating its psychological benefits and their effects on the immune system. When collated this research suggests that performing T'ai chi exercises leads to an improvement of both cell‐mediated immunity and antibody response to infection . However, it should be noted that few studies have demonstrated a unified mechanism behind these improvements – instead focusing on specific players in the immune response such as circulating myeloid dendritic cells or pro‐inflammatory CD14 + CD16 + monocytes…”
Section: Anger Laughter Stress and Tai Chi: Emotion And The Immune mentioning
confidence: 99%
See 1 more Smart Citation
“…T'ai chi ch'uan, an ancient Chinese martial art form that has recently come into vogue in western society has been subject to multiple studies investigating its psychological benefits and their effects on the immune system. When collated this research suggests that performing T'ai chi exercises leads to an improvement of both cell‐mediated immunity and antibody response to infection . However, it should be noted that few studies have demonstrated a unified mechanism behind these improvements – instead focusing on specific players in the immune response such as circulating myeloid dendritic cells or pro‐inflammatory CD14 + CD16 + monocytes…”
Section: Anger Laughter Stress and Tai Chi: Emotion And The Immune mentioning
confidence: 99%
“…When collated this research suggests that performing T'ai chi exercises leads to an improvement of both cell-mediated immunity and antibody response to infection. [28][29][30][31][32][33][34][35][36] However, it should be noted that few studies have demonstrated a unified mechanism behind these improvementsinstead focusing on specific players in the immune response such as circulating myeloid dendritic cells 28,37 or pro-inflammatory CD14 + CD16 + monocytes. 38 Laughter has also been reported to have a surprisingly potent modulating effect on the immune system.…”
Section: Anger Laughter Stress and Tai Chi: Emotion And The Immune mentioning
confidence: 99%
“…And the results proved that the mental measures of VT and MH were significantly improved for college students with Tai Chi intervention. Tai Chi exercise has been reported to have functions in decreasing blood pressure, changing lipid profiles, and improving both cell-mediated immunity and antibody response [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that t'ai chi exercise had favorable effects on cell-mediated immune parameters and antibody responses. 39 …”
Section: Immunologic Effectsmentioning
confidence: 99%